Cooling techniques to improve the machinability and sustainability of light-weight alloys: A state-of-the-art review. (February 2021) - Sarikaya, Murat; Gupta, Munish Kumar; Tomaz, Italo; Danish, Mohd.; Mia, Mozammel; Rubaiee, Saeed; Jamil, Mohd; Pimenov, Danil Yu; Khanna, Navneet
Abstract: A well-acknowledged role of cutting fluids in any cutting operation has made them inevitable to utilize regarding the provision of adequate cooling and lubrication. Mineral-based cutting fluids are common practice in the industry; however, they are not suitable for our ecology and health. Therefore, there is a need to implement sustainable cooling/lubrication system that helps the environment and improves the machinability of light weight alloys. This review is presenting the machining and sustainability characteristics of minimum quantity lubrication (MQL), nanofluids-MQL, Ranque-Hilsch vortex tube MQL (RHVT + MQL), cryogenic-MQL as alternative to flood cooling applications in the cutting of light-weight materials. It can be stated that MQL advancements can offer clear guidelines to implement hybrid cooling techniques to improve heat transfer, lubrication, and sustainable implementations.